2008
DOI: 10.1063/1.2890995
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of stress and morphology in electrodeposited copper nanofilms by cantilever beam method and in situ electrochemical atomic force microscopy

Abstract: Both stress and atomic force microscopy (AFM) measurements were carried out in situ during potentiostatic electrodeposition of copper on gold in 0.05moldm−3 CuSO4 in 0.1moldm−3 H2SO4 with and without additives. With no additives, compressive stress generally developed initially and films subsequently underwent a compressive-to-tensile (C-T) transition. With increasing negative potential, the time for the C-T transition decreased rapidly as the rate of coalescence of nuclei (measured by AFM) increased rapidly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…A compressive stress arises from the rst instants when the potential is applied. The compressive stress is partially due to the dissolution of the copper lm which contains tensile stress 28,29 and to the deposition of HKUST-1 crystals. A compressive stress is in good agreement with the appearance of most MOF layers and HKUST-1 ones in particular: the layers appear to be constituted by continuous lms of intergrown crystals with good adhesion to each other, and while buckling of the layers can be observed, cracks have not been reported for this MOF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A compressive stress arises from the rst instants when the potential is applied. The compressive stress is partially due to the dissolution of the copper lm which contains tensile stress 28,29 and to the deposition of HKUST-1 crystals. A compressive stress is in good agreement with the appearance of most MOF layers and HKUST-1 ones in particular: the layers appear to be constituted by continuous lms of intergrown crystals with good adhesion to each other, and while buckling of the layers can be observed, cracks have not been reported for this MOF.…”
Section: Resultsmentioning
confidence: 99%
“…To determine stresses in MOF lms, rst a 2 mm layer of copper was electrodeposited on the cantilever's gold-coated face causing tensile stress to arise. 29 As a blank, thin lm stress was measured during dissolution of copper in an ethanol/water (67 : 33 vol%) electrolyte without H 3 BTC but with 10 g L À1 methyltributylammonium methyl sulphate (32 mM, MTBS, Sigma-Aldrich, 95%) to enhance the conductivity. The same experiment was repeated with the same electrolyte with 10 g L À1 of H 3 BTC (48 mM) and 10 g L À1 of MTBS (32 mM).…”
Section: Synthesis Of Hkust-1mentioning
confidence: 99%
“…For example, cantilever curvature has been used to quantify the surface stress induced by surface charge (electrocapillarity) [25][26][27][28] and adsorption processes [29][30][31][32] as well as the growth stress associated with upd 25,[33][34][35][36][37][38][39][40][41][42][43][44] and the electrodeposition of bulk thin film. [45][46][47][48][49][50][51][52][53][54][55] This method is particularly useful in identifying structural changes, such as surface alloying, that may proceed without any electrochemical or nanogravimetric signature. 39,42 In the case of Co deposition, Cammarata 53,56 reported that Co, galvanostatically electrodeposited onto amorphous NiTi, shows compressive-tensile-compressive (CTC) stress transitions that are typically observed for Volmer-Weber growth.…”
Section: (H 2 O)]mentioning
confidence: 99%
“…5,[15][16][17] The use of these additives in electrodeposited copper thin films is also known to lead to smaller, more dense grains during film growth 18 . Additives are proposed to decrease surface diffusivity and reduce the number of vacant sites for adatom adsorption 19 .…”
Section: Introductionmentioning
confidence: 99%
“…These stresses are found to evolve during film growth and can consist of a compressive-to-tensile (CT) or (CTC) behaviour in high mobility films during vapour-phase deposition [1][2][3] or tensile behaviour during room-temperature electrodeposition in low-mobility films [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%